Meningkatkan Kompetensi Guru Kelas dalam Pembelajaran melalui Supervisi Akademik di SD Negeri 3 Rumbuk - Anwar, M. Rosihan (Lembaga Yasin AlSys, 2022)
The research background is the low competence of class teachers in the learning process in class. The solution is to streamline the implementation of academic supervision to increase the competence of class teachers in the learning process at SDN 3 Rumbu. In school action research this was carried out in 2 cycles, from the results of the actions taken it was proven to be able to increase the competence of class teachers in the learning process by achieving the set classical completeness of 85%. Classical Completeness 33% obtained in the first cycle, can be increased in the second cycle to 100%. Indicators of research success are; 1) the results of the observations of the school principal and teacher observations during the mentoring process received the title of